Superior Electromechanical Power at Rare‐Earth Manipulated Glassy Morphotropic Phase Transitions - Le Zhang; Liqiang He; Shuyuan Xu; Haoyu Wang; Yunlong Sun; Yating Ran; Dong Wang; Kaiyun Chen; Junkai Deng; Zibin Chen; Danyang Wang; Michael A. Carpenter; et al. (Advanced Science, 2025)
Abstract High‐precision displacement control and the driving joints of artificial intelligence robotics, as well as advanced medical facilities, necessitate the use of superior lead‐free electromechanical materials that exhibit substantial electrostrain and driving force while maintaining thermal stability. In this study, an effective physical approach is developed to achieve significant enhancements of 135% and 50% in symmetric electrostrain and elastic modulus, respectively, of Sm‐doped (Bi,Na)TiO3‐BaTiO3 ceramics within the temperature range of 293–353K. This advancement facilitates a marked improvement in stress output. Unlike the prevalent focus on enhancing symmetric/asymmetric electrostrain output through polar coexistence states and defect dipoles, our approach induces superior electrostrain and stress power by inhibiting the formation of the R3c phase and manipulating the transition pathway in the morphotropic phase boundary composition of (Bi,Na)TiO3‐based ceramics via rare‐earth Sm doping. The achieved reversible glassy P4bm→P4mm and residual R3c→P4mm parallel transition paths, characterized by significant lattice expansion, enable the realization of potential electromechanical power across a broad temperature range. This approach overcomes the limitations of significant elastic softening and the deterioration of electrical properties with temperature variations at specific morphotropic/polymorphic phase transitions. Thus, it offers an effective method for generating superior electromechanical power in lead‐free ferroelectrics.